Design and analysis of a K-band wideband voltage-controlled oscillator with robust start-up and frequency boost - Sun, Junyi (2016)
This study presents a K-band differential voltage-controlled oscillator (VCO) with robust start-up. A hybrid technique that combines open-loop digitally controlled tail current with switchable auxiliary cross-coupled pairs (ACCPs) is proposed to ensure robust start-up for wideband operation. Compared with prior closed-loop current controlling method, the proposed technique does not suffer from phase-noise degradation. Furthermore, by evenly distributing the ACCPs, transistors with smaller size are allowed to achieve the same start-up condition, which leads to frequency boost and phase-noise improvement. Implemented in 0.18 μm complementary metal-oxide-semiconductor technology, the VCO achieves a wide-frequency tuning range of 21.4-26.29 GHz (20.5%) and a low phase noise of -108.8 dBc/Hz at 1 MHz offset from 25.8 GHz carrier frequency. At 1.1 V power supply, the power consumption of the core circuit is 7.9-11.4 mW across the entire output frequency range.